Researching Cognitive Processes of Translation - Li, Defeng; Lei, Victoria Lai Cheng; He, Yuanjian; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This edited volume covers an array of the most relevant topics in translation cognition, taking different approaches and using different research tools. It explores theoretical and methodological issues using case studies and examining their practical and pedagogical implications. It is a valuable resource for translation studies scholars, graduate students and those interested in translation and translation training, enabling them to conceptualize translation cognition, in order to enhance their research methods and designs, manage innovations in their translation training or simply understand their own translation behaviours.
Part I: Neurocognitive Basis for Translation -- 1. Suggestions for a New Interdisciplinary Linguo-cognitive Theory in Translation Studies -- 2. Translating/Interpreting as Bilingual Processing: The Theoretical Framework -- 3. Translation in the Brain: Preliminary Thoughts About a Brain-imaging Study to Investigate Psychological Processes Involved in Translation -- 4. Explore the Brain Activity During Translation and Interpreting Using Functional Near-infrared Spectroscopy -- 5. On Interpreting -- Part II: Behavioural Perspectives -- 6. Segmentation in Translation: A Look at Expert Behaviour -- 7. Translation Competence as a Cognitive Catalyst for Multiliteracy - Research Findings and Their Implications for L2 Writing and Translation Instruction -- 8. Revisiting Processing Time for Metaphorical Expressions: An Eye-tracking Study on Eye-voice Span during Sight Translation -- Part III: Human-Machine Interface: Translation and Post-editing -- 9. Measuring Difficulty in Translation and Post-editing: AReview -- 10. Outline for a Relevance Theoretical Model of Machine Translation Post-editing.
Keywords: Translating and interpreting; Comparative literature; Language Translation; Comparative Literature